How Bacterial Redox Sensors Transmit Redox Signals via Structural Changes - In-Gyun Lee; Bong-Jin Lee (MDPI AG, 2021)
Bacteria, like humans, face diverse kinds of stress during life. Oxidative stress, which is produced by cellular metabolism and environmental factors, can significantly damage cellular macromolecules, ultimately negatively affecting the normal growth of the cell. Therefore, bacteria have evolved a number of protective strategies to defend themselves and respond to imposed stress by changing the expression pattern of genes whose products are required to convert harmful oxidants into harmless products. Structural biology combined with biochemical studies has revealed the mechanisms by which various bacterial redox sensor proteins recognize the cellular redox state and transform chemical information into structural signals to regulate downstream signaling pathways.